PERAN HUMAS DALAM MEMBANGUN CITRA SMK NEGERI 3 SAMPIT - Alivermana Wiguna; Fatimah Setiani; Devi Septia Dennyanti (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
This study aims to determine the implementation of the role of public relations in develoving school’s image of SMK Negeri 3 Sampit.LPPThe type of this study is qualitative descriptive research. The study subjects consists of 4 informants namely Principal, vise principal of public relation, teacher, and committee. The techniques of collecting data are using interviews, observation, and documentation. The analyzing data are by data reduction, data presentation, and conclusion. The data validity procedure are using triangulation techniques sources and methods.The results showed that the implementation of the role of public relations in order to build the image of SMK Negeri 3 Sampit as a whole has gone well, to external and internal public. The media used in publicizing information and attracting public interest in SMK Negeri 3 were directly and indirectly, such as oral, print media (brochures, newspaper Radar Sampit, and smart magazines), online media (facebook and website, Whats App), Broadcasting media (radio and television), special events (carrying out promotions to junior high schools coordinated by public relations), and installing banners on certain streets.